Development of 3D gait analyzer software based on marker position data. - Mihradi, Sandro; Henda, Agri I.
Human walking analysis is instrumental in medical rehabilitation because it provides quantitative information of human body segment during walking. The present work is a part of a research on the development of 3Dgait analyzer software. The software consists of a program to process and display3Dkinematicsand kinetics parameters of human gait based on position of external skin markers as a function of time in X, Y, Z axis and anthropometric data of a subject.To achieve good results,the marker position data is initially smoothed to eliminate noises before further processing. A graphical user interface is also constructed in this work for ease of use of the program and to enable presenting the results readily.The program developed in the present research could successfully calculate parameters of human gait such as spatio temporal parameters, linear kinematics,angular kinematics of joints,as well as ground reaction and joint forces.
Keywords: 3D Kinematics; 3D Kinetics; Gait Analysis; Human body model; Inverse dynamics